2021
DOI: 10.3389/fcell.2021.663032
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically Anchored mRNA and miRNA Expression Profiling in Zebrafish Reveals Flame Retardant Chemical Toxicity Networks

Abstract: The ubiquitous use of flame retardant chemicals (FRCs) in the manufacture of many consumer products leads to inevitable environmental releases and human exposures. Studying toxic effects of FRCs as a group is challenging since they widely differ in physicochemical properties. We previously used zebrafish as a model to screen 61 representative FRCs and showed that many induced behavioral and teratogenic effects, with aryl phosphates identified as the most active. In this study, we selected 10 FRCs belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…Clusters 1 (orange) and 2 (red) represented all the flame retardant chemicals (FRCs) examined and were also more similar to each other than to other clusters in the dataset, showing that the overall transcriptomic response to FRCs is distinct from PAH and TCDD responses. In addition to differences in transcriptomic response based on chemical type, we also found that when we compared our clustering to our lab’s previous studies investigating the morphology and behavior effects caused by FRC exposure [ 6 , 41 ], there were differences between transcriptomic response and developmental toxicity phenotype. For example, IPP exposure caused both morphology and behavior malformations at 120 hpf and yet, it clustered here with the relatively benign FRCs.…”
Section: Resultsmentioning
confidence: 70%
See 4 more Smart Citations
“…Clusters 1 (orange) and 2 (red) represented all the flame retardant chemicals (FRCs) examined and were also more similar to each other than to other clusters in the dataset, showing that the overall transcriptomic response to FRCs is distinct from PAH and TCDD responses. In addition to differences in transcriptomic response based on chemical type, we also found that when we compared our clustering to our lab’s previous studies investigating the morphology and behavior effects caused by FRC exposure [ 6 , 41 ], there were differences between transcriptomic response and developmental toxicity phenotype. For example, IPP exposure caused both morphology and behavior malformations at 120 hpf and yet, it clustered here with the relatively benign FRCs.…”
Section: Resultsmentioning
confidence: 70%
“…This was done using a large array of transcriptomic data combined with the first chemical-focused gene co-expression network inferred using zebrafish. Transcriptomic data from 48-h post fertilization (hpf) zebrafish included several previously published studies [ 7 , 39 41 ] in addition to new unpublished datasets. Details on these datasets including the exposure concentrations and the number of differentially expressed genes (DEGs) are included in Supplementary Table S 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations